Inside Cover. Issue 4 (3rd April 2022) - Kong, Yawei; Zhao, Yinping; Yu, Yao; Su, Wenhua; Liu, Zhijia; Fei, Yiyan; Ma, Jiong; Mi, Lan
Abstract : The ability to sort yeast cells is important for diverse applications in the industry and research. We determined the aging level of yeast by the fluorescence lifetime imaging microscopy (FLIM) by an endogenous fluorophore NAD(P)H, which was label‐free and non‐invasive. Young and active yeast cells were sorted by the laser‐induced forward transfer (LIFT) system at the single cell level. The high viability of sorted cells was achieved. Further details can be found in the article by Yawei Kong, Yinping Zhao, Yao Yu, Wenhua Su, Zhijia Liu, Yiyan Fei, Jiong Ma, and Lan Mi (e202100344 ) Abstract : The ability to sort yeast cells is important for diverse applications in the industry and research. We determined the aging level of yeast by the fluorescence lifetime imaging microscopy (FLIM) by an endogenous fluorophore NAD(P)H, which was label‐free and non‐invasive. Young and active yeast cells were sorted by the laser‐induced forward transfer (LIFT) system at the single cell level. The high viability of sorted cells was achieved. Further details can be found in the article by Yawei Kong, Yinping Zhao, Yao Yu, Wenhua Su, Zhijia Liu, Yiyan Fei, Jiong Ma, and Lan Mi (e202100344 )